Factors Influencing Peers' Attitudes towards Students with Special Needs in Indonesia : The Role of Moral Identity, Empathy, Age, and Gender - Josiana Levyadi; Farida Kurniawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the factors influencing peer attitudes towards students with special educational needs and disabilities (SEND), seen from the role of moral identity, empathy, age, and gender. This study uses a quantitative approach with a non-experimental method of cross-sectional design. The respondents were 288 Indonesian students aged 18-25(M = 19.67 years, SD = 1.23), with 62.9% female and 37.1% male. The instrument used was a questionnaire distributed via social media, and the data was analyzed by correlation analysis, ANOVA, and SEM. The results showed that age did not correlate with attitudes towards college students with SEND. There is no difference between male and female students. Moral identity was negatively associated with negative attitudes towards college students with SEND, both in total, affective, cognitive, and behavioral dimensions. The dimensions of fantasy, perspective-taking, and empathic concern can mediate the relationship between the two. The results of the study provide implications for increasing positive peer attitudes towards college students with SEND by encouraging the development of moral identity and empathy.